2005
DOI: 10.1002/ijc.21102
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of laminin α4 chain expression inhibits glioma invasionin vitro andin vivo

Abstract: The laminin family is a structural constituent of the extracellular matrix that plays an essential role in promoting the motility of infiltrative tumor cells. We investigated the role of laminin a4 chain, a subset of laminin-8, -9 and -14, in the motile and invasive activities of human glioma cells. All malignant glioma cell lines examined expressed more mRNA for the laminin a4 and b1 chains than for the b2 chain, indicating that these cells predominantly express the laminin-8 isoform. Introducing an antisense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Laminin-4 (LAMA4) has been reported to be highly upregulated in hepatocellular carcinoma and the downregulation of LAMA4 could inhibit glioma invasion. 22,23 Interestingly, in our study, we found LAMA4 was overexpressed in Gadd45a -/-MEF cells. As another important component of BM, collagens also play curial roles in tumorigenesis.…”
Section: Gadd45a Decreases Migration and Invasion Abilities Of Hepg2 mentioning
confidence: 46%
“…Laminin-4 (LAMA4) has been reported to be highly upregulated in hepatocellular carcinoma and the downregulation of LAMA4 could inhibit glioma invasion. 22,23 Interestingly, in our study, we found LAMA4 was overexpressed in Gadd45a -/-MEF cells. As another important component of BM, collagens also play curial roles in tumorigenesis.…”
Section: Gadd45a Decreases Migration and Invasion Abilities Of Hepg2 mentioning
confidence: 46%
“…The brain slice model enabled us to evaluate the invasion of glioma cells into the surrounding brain tissue in conditions analogous to those of normal brain in situ. We implanted a rhodamine-labeled spheroid of each glioma cell onto the corpus callosum of the cerebral hemisphere (22). Glioma cells transfected with control siRNA or without siRNA actively migrated and infiltrated into the brain tissue around tumor spheroids, whereas glioma cells treated with SPARC siRNA showed decreased migration into the surrounding normal brain tissue (Fig.…”
Section: Suppression Of Sparc Expression Inhibits Glioma Cell Invasiomentioning
confidence: 99%
“…[27][28][29][30] Furthermore, Lm a4 chain is characteristic of invasive gliomas, and inhibition of Lm a4 chain by antisense RNA seems to prevent tumor invasion and angiogenesis. 32,35,36 A similar characteristic has as also been described for SPARC. 69 In summary, the results of present study show that a4 chain Lms are widely expressed in oncocytomas and RCCs.…”
Section: Adhesion and Migration Of Rccs On Recombinant Lm-411mentioning
confidence: 48%
“…[27][28][29][30] Overexpression of Lm a4 chain, on the other hand, has been suggested to promote angiogenesis, 31,32 and to correlate with malignancy and invasive capacity in human gliomas. [33][34][35][36] Tissue-specific inhibition of Lm a4 chain expression with antisense oligonucleotides has been suggested to be a potential new treatment for gliomas and tumor angiogenesis. 32,37 The role of a4 chain Lms in carcinomas has remained largely unresolved.…”
mentioning
confidence: 99%